2008
DOI: 10.2478/s11536-007-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Successful discontinuation of insulin treatment after gestational diabetes is shown to be a case of MODY due to a glucokinase mutation

Abstract: AbstractWe describe a woman who first presented with gestational diabetes at 26 weeks gestation and was managed with insulin. Following delivery of a healthy baby she had an abnormal OGTT (oral glucose tolerance test) 6 weeks post partum and was managed with diet. In her second pregnancy she was diagnosed with gestational diabetes at 10 weeks and required insulin. Following delivery she was again managed on diet alone. Four years later, during her third pregnancy, she was manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We originally posed the question of what is the impact of pharmacological and non-pharmacological glucose lowering therapy in GCK-related hyperglycemia. However, we identified only one case report that presented data on active pharmacological intervention 12 and one study on dietary intervention 13 and the rest of the 10 studies [14][15][16][17][18][19][20][21][22][23] assessed the impact of stopping anti-hyperglycemic agents on HbA1c or glucose or assessed the stability of HbA1c over time on no therapy (Table 3). Thus, we concentrated on analyzing the evidence to support or refute non-treatment of GCK-related hyperglycemia.…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…We originally posed the question of what is the impact of pharmacological and non-pharmacological glucose lowering therapy in GCK-related hyperglycemia. However, we identified only one case report that presented data on active pharmacological intervention 12 and one study on dietary intervention 13 and the rest of the 10 studies [14][15][16][17][18][19][20][21][22][23] assessed the impact of stopping anti-hyperglycemic agents on HbA1c or glucose or assessed the stability of HbA1c over time on no therapy (Table 3). Thus, we concentrated on analyzing the evidence to support or refute non-treatment of GCK-related hyperglycemia.…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%
“…Most studies on GCK-related hyperglycemia looked at within individual stability of HbA1c over time without glucose lowering therapy (175 individuals from case reports and cohort data, range of time between 3-126 months) 14,16,18,[20][21]23 or after cessation of pharmacologic therapy following genetic diagnosis (35 individuals from case reports and cohort data) 15,[19][20][22][23] . All studies showed stability of HbA1c with no significant change including when glucose lowering therapy of either oral hypoglycemic agents (OHA) or insulin was discontinued (table 3).…”
Section: A) Gck-related Hyperglycemiamentioning
confidence: 99%